An Influence of Organizational Culture and Supervision on Employee Performance Matahari Department Store Medan Fair - Fauziah Astuti; Rusiadi; Bachtiar Efendi (CERED Indonesia Institute, 2022)
This study aims to analyze the influence of organizational culture and supervision on the performance of the employees of the Matahari Department Store Medan Fair. The data collected in this study were primary data and secondary data, which were collected through data collection instruments in the form of questionnaires, interviews and documentation studies. The sample in this study were 70 respondents. This study uses quantitative data, with multiple linear regression analysis method. The test results show that partially the organizational culture variable has a positive and significant effect on employee performance. Supervision variable has a positive and significant effect on employee performance. Meanwhile, simultaneously, the variables of organizational culture and supervision have a positive and significant effect on company performance.